Termination Analysis of Cooperation Agreement between Bekasi City Government & PT. Kitita Alami Propertindo on the Revitalization & Management of Pondok Gede Market - Safitri Saraswati; Noor Saptanti; Jadmiko Anom Husodo (JURNAL AKTA, 2024)
The termination of the cooperation agreement between the Bekasi City Government and PT. Kitita Alami Propertindo regarding the revitalization and management of Pondok Gede Market has attracted attention because it involves public interest and complex regulations. This study aims to legally analyze the aspects underlying the unilateral termination of the agreement by the Bekasi City Government due to default by PT. Kitita Alami Propertindo. The research method used is a normative legal approach, which examines the legal aspects of the cooperation agreement with a focus on default and legal procedures for terminating the agreement. The results of the study indicate that the agreement can be unilaterally terminated by the government based on default, but there are legal risks that need to be considered, especially in fulfilling the rights of third parties. In conclusion, the termination of the cooperation agreement in this legal context has implications for both parties, and requires the application of strict rules in resolving contract disputes.